Projeto principal de educação para América Latina e o Caribe (PPE 1980-2000) e alfabetização de adultos - Dornfeld, Larissa Mendes Gontijo (2024)
The thesis aims to analyze the recommendations for adult literacy in the first ten years of development of the Major Project of Education for Latin America and the Caribbean approved by the United Nations Educational, Scientific and Cultural Organization for implementation in the period from 1980 to 2000. The thesis targets three literacy experiences in Latin America and the Caribbean: Argentina, Nicaragua, and Cuba. It takes as its theoretical-methodological framework concepts of history based on Le Goff (2010) and Bloch (1963) and dialogues with other authors to produce this research. It adopts the methodology of historical research and, thus, examines twenty bulletins by United Nations Educational, Scientific and Cultural Organization during the first ten years of the project, as well as texts produced by this organization during the period. The thesis concludes that thinking of literacy as an ally of economic and social development, as advocated in the PPE (1980-2000), does not contribute to the construction of a more just world for all, since such a purpose only helps to maintain, in the past and present, a world economic order founded on the exploitation of the poor (countries and people) and inequalities.